Philippines : Study on Agribusiness, Infrastructure, and Logistics for Growth in Mindanao - World Bank (Washington, DC, 2014)
The World Bank has carried out a study on agribusiness, logistics, and infrastructure for growth in Mindanao. Funded by the Australian Agency for International Development, the study aimed to understand better why the Philippines, with its well-educated human capital and diverse natural resource base, significantly lags behind the rest of East Asia in per capita growth. Some rural areas with high agricultural potential, such as Mindanao and, to some extent, the Visayas, also lag behind the rest of the Philippine economy. The study sought to understand how the Philippines could improve its competitiveness in agribusiness and agriculture commodity markets, areas where Mindanao enjoys strong comparative advantages. The study analyzed the constraints affecting the performance of agricultural value chains in Mindanao, particularly in terms of infrastructure and logistics. The agricultural commodities selected were corn and bananas because of their economic weight at regional and national levels. Mindanao, especially the Bukidnon plateau, is a major producer of white and yellow corn. The study focused on yellow corn, which is grown mainly for animal feed and used in milled and non-milled varieties. Mindanao is also the country's main banana producing region, both for export and for the domestic market. Region eleventh (the Davao region) is the leading banana producer and supplier of export-quality bananas in the country. In recent years, the Philippines have become the world's second top exporter of Cavendish bananas.